Climate shocks and choice of adaptation strategy for Kenyan maize-legume farmers: Insights from poverty, food security and gender perspectives - Tongruksawattana, Songporne (2014)
Climate change is a serious threat for agriculture, food security and the fight against poverty, especially in sub-Saharan Africa. With the IPCC climate outlook for the 21st century, the future of maize production in Kenya remains under threat of more intense and frequent droughts, fluctuations in temperature and more erratic rainfall patterns. Effective adaptation to these progressive changes in climatic condition is the key to securing food production and livelihoods for millions of poor people. This study was conducted to provide a comprehensive understanding of the adaptation behaviour of maize-legume farm households in response to climate shocks, with emphasis on poverty, food security and gender perspectives. The research was conducted in rural Eastern and Western Kenya for the “Sustainable Intensification of Maize-Legume Farming Systems for Food Security in Eastern and Southern Africa (SIMLESA)” project.